The Utilization of Educational Technology to Improve the Bilingual Abilities of Elementary School Children: A Case Study of First and Second Language Interaction - Dwanda Putra, Lovandri; Nur Rahmi, Sri; Farah, Rina (International Journal of Language and Ubiquitous Learning, 2025)
Background. Educational technology is increasingly being used to support bilingual learning in elementary school children. The interaction between first and second languages in the context of education is still a challenge in formal learning. The use of technology is expected to be able to improve children's bilingual skills without reducing their first language competence. Purpose. This study aims to analyze the effectiveness of educational technology in improving the bilingual ability of elementary school children and understanding the interaction between first and second languages in the learning process. The study also explores the factors that contribute to the success of technology-based bilingual learning. Method. The research method uses a quantitative approach with a pseudo-experimental design. The sample consisted of elementary school students who were divided into control and experimental groups. The instruments used included language tests, observations, and interviews with teachers and parents. Data were analyzed using statistical tests to measure improvement in bilingual skills before and after technological interventions. Results. The results of the study show that the use of educational technology significantly improves children's bilingual skills. Second language scores increased higher than first languages, but without causing a decrease in first language competence. The factors of the duration of technology use, teacher guidance, and parental support play an important role in the effectiveness of technology-based bilingual learning. Conclusion. The conclusion of this study confirms that technology can be an effective tool in increasing bilingualism in elementary school children if used in a directed manner and supported by a conducive learning environment. The implications of this research provide new insights for the development of technology-based curriculum as well as the development of language learning applications that are more balanced in accommodating the first and second languages.